Pengangguran Usia Muda dan Terdidik di Kalimantan Tengah - Nurafny Indrawati; Lidiae Lidiae; Alexandra Hukom (Jurnal Inovasi Ekonomi Syariah dan Akuntansi, 2024)
Educated unemployment in Indonesia is increasing, this phenomenon occurs when young, highly educated individuals find it difficult to get jobs according to their qualifications. In Central Kalimantan the proportion of educated unemployed will increase because low-educated workers still dominate labor absorption. This research aims to understand the factors that cause youth and educated unemployment in depth, which is important in order to formulate appropriate solutions, both from the government, educational institutions and individuals. Binary logistic regression is the analytical tool used in this research. The results obtained state that education level and gender have a positive and significant effect on the unemployment status of young and educated people in Central Kalimantan Province. Meanwhile, the Age variable has a negative and insignificant effect on the unemployment status of young and educated people in Central Kalimantan Province. And the location variable has a negative and significant influence on the unemployment status of young and educated people in Central Kalimantan Province.